2021
DOI: 10.3389/fmicb.2021.655873
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Floating Biofilm Formation and Phenotype in Synovial Fluid Depends on Albumin, Fibrinogen, and Hyaluronic Acid

Abstract: Biofilms are typically studied in bacterial media that allow the study of important properties such as bacterial growth. However, the results obtained in such media cannot take into account the bacterial localization/clustering caused by bacteria–protein interactions in vivo and the accompanying alterations in phenotype, virulence factor production, and ultimately antibiotic tolerance. We and others have reported that methicillin-resistant or methicillin-susceptible Staphylococcus aureus (MRSA or MSSA, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 32 publications
4
32
0
Order By: Relevance
“…According to this mechanism, small planktonic aggregates would rapidly reach and stick to the surface, while larger aggregates would take longer to reach the surface and attach to it due, for instance, to the “cellular crowd” hindrance in the medium or to its viscosity. This mechanism is partially confirmed by the observation that sessile biofilm grown in BSF presented a similar extracellular matrix phenotype to planktonic aggregates formed above it [ 1 , 13 ]. In other words, we propose that in physiological media, planktonic and sessile multicellular communities are not developed independently but are rather two interlinked phases of the same developmental process.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…According to this mechanism, small planktonic aggregates would rapidly reach and stick to the surface, while larger aggregates would take longer to reach the surface and attach to it due, for instance, to the “cellular crowd” hindrance in the medium or to its viscosity. This mechanism is partially confirmed by the observation that sessile biofilm grown in BSF presented a similar extracellular matrix phenotype to planktonic aggregates formed above it [ 1 , 13 ]. In other words, we propose that in physiological media, planktonic and sessile multicellular communities are not developed independently but are rather two interlinked phases of the same developmental process.…”
Section: Discussionmentioning
confidence: 75%
“…Because of their subtle symptomatology and treatment recalcitrance, PJIs are true clinical challenges. Biofilm formation is thought to be a key player of this type of bacterial recalcitrance [ 10 , 12 , 13 , 27 ]. Our previous investigation, based on ex vivo analysis [ 1 ], suggested that staphylococcal behavior is sharply different in physiological fluids as compared with commercial broths, particularly in two aspects: the presence of planktonic aggregates and a considerable phenotypic reorganization of the sessile biofilm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, synovial fluid-induced aggregation of Staphylococcus aureus has been heavily investigated as a bacterial survival mechanism in the development of periprosthetic joint infections (PJI). Numerous in vitro studies have provided novel insights into both the composition and pathogenic attributes of staphylococcal aggregates(1),(2),(3),(4),(5). It is now evident that aggregation occurs rapidly upon contact with synovial fluid and confers considerable recalcitrance to antibiotic administration (1),(3),(6)(7).…”
Section: Introductionmentioning
confidence: 99%